Rapid Gene Evolution in an Ancient Post-transcriptional and Translational Regulatory System Compensates for Meiotic X Chromosomal Inactivation. - Xia, S.; Ventura, I.M.; Blaha, A.; Sgromo, A.; Han, S.; Izaurralde, E.; Long, M. (Molecular Biology and Evolution, 2022)
It is conventionally assumed that conserved pathways evolve slowly with little participation of gene evolution. Nevertheless, it has been recently observed that young genes can take over fundamental functions in essential biological processes, for example, development and reproduction. It is unclear how newly duplicated genes are integrated into ancestral networks and reshape the conserved pathways of important functions. Here, we investigated origination and function of two autosomal genes that evolved recently in Drosophila: Poseidon and Zeus, which were created by RNA-based duplications from the X-linked CAF40, a subunit of the conserved CCR4-NOT deadenylase complex involved in posttranscriptional and translational regulation. Knockdown and knockout assays show that the two genes quickly evolved critically important functions in viability and male fertility. Moreover, our transcriptome analysis demonstrates that the three genes have a broad and distinct effect in the expression of hundreds of genes, with almost half of the differentially expressed genes being perturbed exclusively by one paralog, but not the others. Co-immunoprecipitation and tethering assays show that the CAF40 paralog Poseidon maintains the ability to interact with the CCR4-NOT deadenylase complex and might act in posttranscriptional mRNA regulation. The rapid gene evolution in the ancient posttranscriptional and translational regulatory system may be driven by evolution of sex chromosomes to compensate for the meiotic X chromosomal inactivation (MXCI) in Drosophila.